Accurate and Real‐Time Detection Method for the Exothermic Behavior of Enzymatic Nano‐Microregions Using Temperature‐Sensitive Amino‐AgInS2 Quantum Dots. Issue 1 (10th November 2021) - Zhang, Hui; Wu, Youshen; Tang, Peng; Zhu, Hongrui; Gan, Zhenhai; Zhang, Hu‐Qin; Wu, Daocheng
Abstract: The thermal behavior of enzymes in nanoscale is of great significance to life phenomena. This nonequilibrium state real‐time thermal behavior of enzymes at nanoscale cannot be accurately detected by existing methods. Herein, a novel method is developed for the detection of this thermal behavior. The enzyme‐quantum dot (QD) conjugates can be obtained by chemically grafting temperature‐sensitive amino‐AgInS2 QDs to the enzyme, where the QDs act as nanothermometers with a sensitivity of −2.82% °C −1 . Detecting the photoluminescence intensity changes of the enzyme‐QD conjugates, the real‐time thermal behavior of enzymes can be obtained. The enzyme‐QD conjugates show a temperature difference as high as 6 °C above ambient temperature in nano‐microregions with good reproducibility (maximum error of 4%) during catalysis, while solution temperature hardly changed. This method has a temperature resolution of ≈0.5 °C with a detection limit of 0.02 mg mL −1 of enzyme, and spatially ensured that the amino‐AgInS2 QDs are quantitatively bound to the enzyme; thus, it can accurately detect the exothermic behavior of the enzyme and can be extended to other organisms' detection. This method has high sensitivity, good stability, and reliability, indicating its great potential application in investigating the thermal behavior of organisms in nanoscale and related life phenomena. Abstract : Temperature‐sensitive amino‐AgInS2 quantum dots (QDs) are grafted onto lipase via glutaraldehyde to form lipase‐QD conjugates. With the addition of the substrate in lipase‐QDs solution, the heat generated by the substrate decomposition in nanoscale is detected in real‐time by the QDs, accompanied by a decrease in photoluminescence intensity, demonstrating the nano‐microregions exothermic behavior of the enzymatic reaction in real time.